2022
DOI: 10.3389/fgene.2022.783016
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Prognostic Relevance of Differential Claudin Gene Expression Highlights Claudin-4 as Being Suppressed by TGFβ1 Inhibitor in Colorectal Cancer

Abstract: Background: Claudins (CLDNs) are a family of closely related transmembrane proteins that have been linked to oncogenic transformation and metastasis across a range of cancers, suggesting that they may be valuable diagnostic and/or prognostic biomarkers that can be used to evaluate patient outcomes. However, CLDN expression patterns associated with colorectal cancer (CRC) remain to be defined.Methods: The mRNA levels of 21 different CLDN family genes were assessed across 20 tumor types using the Oncomine databa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(19 citation statements)
references
References 68 publications
(77 reference statements)
0
19
0
Order By: Relevance
“…Although there are conflicting reports regarding CLDN1 expression in CRC, the majority of data suggests that CLDN1 is upregulated in CRC. At the RNA level, seventeen independent groups reported the upregulation of CLDN1 in CRC compared to the normal colon [ 34 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 ]. This upregulation was found to occur at all stages of CRC, including metastases [ 41 , 42 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although there are conflicting reports regarding CLDN1 expression in CRC, the majority of data suggests that CLDN1 is upregulated in CRC. At the RNA level, seventeen independent groups reported the upregulation of CLDN1 in CRC compared to the normal colon [ 34 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 ]. This upregulation was found to occur at all stages of CRC, including metastases [ 41 , 42 ].…”
Section: Resultsmentioning
confidence: 99%
“…When comparing CLDN2 expression in CRC to the normal colon, there is complete agreement among multiple groups that the average CLDN2 RNA levels are upregulated in CRC [ 36 , 39 , 42 , 43 , 48 , 73 , 74 , 75 , 77 ]. Similar RNA upregulation was also found to be true in adenomas (n = 42) compared to the normal colon [ 36 ].…”
Section: Resultsmentioning
confidence: 99%
“…Studies have reported that lower CLDN23 mRNA levels are associated with poorer OS. [40,57] There is also a Cox multivariate survival analysis showing that when CLDN23 is low expressed, the OS of gastric cancer patients is longer. [58] A recent study showed that low expression of CLDN23 was associated with longer OS in colorectal cancer patients of CMS4 and C4 subtypes.…”
Section: Discussionmentioning
confidence: 99%
“…Both overall survival (OS) and disease-free survival (DFS) results were obtained through the GEPIA website. 22 High and low GIT1 expression groups were established based on the median level of GIT1. The association between GIT1 levels and pan-cancer survival outcome was detected using the log-rank test.…”
Section: Survival and Prognosismentioning
confidence: 99%
“…[18][19][20][21] A previous study found that the suppression of GIT1 inhibits breast cancer cell inva sion and metastasis via the upregulation of miR-149. 22 Recently, a report demonstrated that GIT1 is reduced in ER(−) breast cancer when compared to ER(+) cancer, and that higher GIT1 expression implied a better prognosis in ER(−) breast cancer patients. 11 Thus, GIT1 appears to have distinct functions in the growth and migration of breast cancer cells.…”
Section: Introductionmentioning
confidence: 99%